1985
DOI: 10.1007/bf00293164
|View full text |Cite
|
Sign up to set email alerts
|

SCE induction and harlequin staining in mycoplasma-contaminated Chinese hamster cells

Abstract: Chinese hamster V79 and CHO cells infected with Mycoplasma hyorhinis show elevated sister-chromatid exchange (SCE) levels but normal cell proliferation and levels of chromosomal aberrations when compared with uninfected cells. Harlequin staining patterns differ from those seen with uninfected cells at similar levels of bromodeoxyuridine (BrdUrd), indicating that BrdUrd is rapidly depleted from the medium by the mycoplasmal uridine phosphorylase and therefore becomes unavailable over the two cell cycles necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Until recently, cell lines maintained in in vitro cultures have often been infected with mycoplasmas in many laboratories [17,13]. Since rauch information on the antitumor defense mechanism has been obtained from in vitro experiments employing cultured tumor cells, it is important to determine whether and how mycoplasma infection of tumor cells leads to confusing results.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, cell lines maintained in in vitro cultures have often been infected with mycoplasmas in many laboratories [17,13]. Since rauch information on the antitumor defense mechanism has been obtained from in vitro experiments employing cultured tumor cells, it is important to determine whether and how mycoplasma infection of tumor cells leads to confusing results.…”
Section: Introductionmentioning
confidence: 99%
“…In domestic animals the SCE studies are less numerous than those reported in humans but they have been developed in cattle (PoPESCU 1978;DI BERARDINO and SHOFFNER 1979;McFEE and LONG 1982;DI BERAR-DINO et al 1983;LIEBENGUTH and THIEL 1986;ARRUGA et al 1987), pigs (WHITE and OcKEY 1985;RuBES 1987) and ewes (McFEE and SHERRIL 1979) principally.…”
Section: Introductionmentioning
confidence: 99%